Sosialisasi Hak Tenaga Kerja Yang Dirumahkan Akibat Pandemi Covid-19 Di PT.Global Retailindo Pratama - Gawati, Veren Kris; Antari, Putu Eva Ditayani (Universitas Merdeka Pasuruan, 2020)
AbstractCovid-19 pandemic is a virus that attacks the human respiratory system and can be transmitted only to humans. This type of virus has become epidemic in Indonesia and even the whole world, the impact is extraordinary because it has killed tens of thousands of people in Indonesia and also throughout the world. In addition to having an impact on health, this virus also has an impact on economic aspects including the Indonesian economy, which has reduced company productivity and even stopped several business sectors such as in the field of tourism, retail, restaurants and others. Because the impact on business activities is extraordinary, resulting in millions of workers losing their income due to being laid off and terminated by employers. Because the workforce has been laid off and / or terminated by the employer of the employer, legal protection is needed for his rights so that the worker concerned continues to earn income during the co-19 pandemic. According to the Circular of the Minister of Manpower Number 05 / M / BW / 1998 of 1998 concerning wages of workers who were laid off not in the direction of termination of employment, the worker will get full wages for each month and if the employer does not have the ability to pay in full then it needs to be negotiated with workers regarding wages, how they are paid and how long they are laid off. It can also be seen from the Circular of the Minister of Manpower No. SE-907 / MEN / PHI-PPHI / X / 2004 concerning Prevention of Termination of Mass Employment. Whereas for workers who are terminated from employment, it can be seen from Law No. 13 of 2003 concerning Manpower.Keywords: Labor Rights, Pandemi Covid-19AbstrakPandemi Covid-19 merupakan virus yang menyerang pada sistem pernafasan manusia dan dapat menular hanya pada manusia. Jenis virus ini telah mewabah diIndonesia bahkan seluruh dunia, dampaknya luar biasa karena telah menewaskan puluhan ribu manusia di Indonesia dan juga di seluruh dunia. Selain berdampak pada kesehatan, virus ini juga berdampak pada aspek ekonomi termasuk perekonomian Indonesia yaitu telah menurunkan produktivitas perusahaan bahkan hingga menghentikan beberapa sektor usaha seperti dalam bidang parisiwata, ritail, restoran dan lainnya. Karena dampaknya terhadap kegiatan usaha yang luar biasa sehingga mengakibatkan jutaan tenaga kerja kehilangan penghasilan akibat dirumahkan dan diputuskan hubungan kerja oleh pengusaha. Karena tenaga kerja telah dirumahkan dan/atau diputuskan hubungan kerja oleh pengusaha maka diperlukan perlindungan hukum atas hak-haknya agar pekerja yang bersangkutan tetap memperoleh penghasilan selama masa pandemi covid-19. Menurut Surat Edaran Menteri Ketenagakerjaan Nomor 05/M/BW/1998 tahun 1998 tentang upah pekerja yang dirumahkan bukan ke arah pemutusan hubungan kerja maka bagi pekerja tersebut akan mendapatkan upah penuh untuk setiap bulannya dan apabila pengusaha tidak mempunyai kemampuan membayar secara penuh maka perlu dirundingkan dengan pekerja mengenai besarnya upah, cara pembayarannya dan lamanya waktu dirumahkan. Selain itu juga dapat dilihat dari Surat Edaran Menteri Tenaga Kerja No. SE-907/MEN/PHI-PPHI/X/2004 tentang Pencegahan Pemutusan Hubungan Kerja Massal. Sedangkan bagi tenaga kerja yang diputuskan hubungan kerja maka dapat ditinjau dari Undang-undang No.13 Tahun 2003 tentang Ketenagakerjaan.Kata Kunci: Hak Tenaga Kerja, Pandemi Covid-19.